Statins and its Effects on Lipids and Glycemic Status: A Quasi-Experimental Study - Sikandar Hayat Khan; Rahat Shahid; Hafeez, Ayesha; Gillani, Mehreen; Qureshi, Zeeshan Ali; Hafeez, Javeria (Pakistan Armed Forces Medical Journal, 2024)
Objective: To measure changes in lipid and glucose parameters after initiating statin therapy.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Pathology and Medicine, Naval Hospital, Islamabad Pakistan, from Nov 2018 to Oct 2020.Methodology: Thirty-nine male individuals participated in the study after a detailed explanation and consenting procedure. At the outset of the study, baseline testing of fasting plasma glucose and lipid parameters was done. Participants were then started with 10 mg of Atorvastatin/day for six weeks, with visits every two weeks for testing for lipids and glucose.Results: The mean age of participants was 42.47+11.65 years. %Δ (change) in mean (X) from baseline to result of last reading at six weeks for various evaluated parameters were as: %ΔX Fasting plasma glucose = +91.45, %ΔX total cholesterol=-139.63, %ΔX fasting triglycerides=-1.04%ΔX LDLc= -150.49 and %ΔXHDLc= -105.25. For HDLC, 14/31 showed a rise in levels compared to 17/31, who demonstrated a downward trend after starting statin therapy, indicating a differential response among subjects taking statin therapy.Conclusion: Mean glucose levels increased from baseline to six weeks, whereas the mean of all lipid indices (including HDLc) declined in subjects on statin therapy.